Incidence of intravascular hemolysis after transcatheter mitral valve repair. (25th November 2020) - Paulus, M; Meindl, C; Hamerle, M; Schach, C; Maier, L.S; Birner, C; Debl, K; Unsoeld, B
Abstract: Background: Chronic subclinical intravascular hemolysis is a common complication after valve replacement associated with worse prognosis, occurring in up to 80% of patients after mitral valve surgery. While serious intravascular hemolysis after MitraClip implantation has been reported anecdotally, data on the impact of transcatheter mitral valve repair on the prevalence of subclinical hemolysis are lacking. Methods and results: From August 2017 to November 2019, 77 patients with high perioperative risk and moderate-to-severe or severe mitral regurgitation were prospectively enrolled in a single-center trial. All participants were treated with transcatheter edge-to-edge mitral valve repair using the MitraClip NT, NTR or XTR system. Before and three months after the procedure, all patients underwent comprehensive clinical assessment including laboratory measurement of hemoglobin, haptoglobin and lactic acid dehydrogenase in venous blood samples. Presence of subclinical intravascular hemolysis was defined as hemoglobin <13.8 g/dl for males or <12.4 g/dl for females, haptoglobin <65 mg/dl and lactic acid dehydrogenase >250 U/l. Levels of the hemolysis marker haptoglobin significantly decreased three months after the intervention (127±71 mg/dl at three months vs. 158±73 mg/dl at baseline, p<0.001), accompanied by an increase in lactic acid dehydrogenase (251±88 U/l vs. 222±55 U/l, p<0.01), implying the induction of intravascular hemolysis by transcatheter mitral valve repair. Higher residual mitral regurgitation was associated with lower haptoglobin levels three months after mitral valve repair (p<0.05), hinting that shear stress caused by regurgitation flow is the primary mechanism for hemolysis after MitraClip implantation. Concurrently, we observed a trend towards an increase in the presence of subclinical intravascular hemolysis (9.1% at three months vs. 3.9% at baseline, p=0.289). Hemoglobin levels remained unchanged (12.1±1.5 g/dl at three months vs 12.3±1.8 g/dl at baseline, p=0.107). No patient needed treatment for intravascular hemolysis. Conclusion: Transcatheter edge-to-edge mitral valve repair in a high-risk collective is associated with the induction of hemolysis. Yet, prevalence of subclinical intravascular hemolysis is low when compared to mitral valve surgery, emphasizing the good safety profile of minimal-invasive mitral valve therapy. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): ReForM-B research grant, University of Regensburg